2018
DOI: 10.1097/md.0000000000009697
|View full text |Cite|
|
Sign up to set email alerts
|

Tuina for children with cerebral palsy

Abstract: Background:Cerebral palsy (CP) describes a group of permanent disorders of movement and posture causing activity limitations, leading the most common movement disorder to children. On recovery of various aspects of CP, massotherapy has a good effect in a great many of Chinese clinical trials. Therefore, we plan to conduct a protocol of systematic review aimed at systematically reviewing all the clinical evidence on the effectiveness of massotherapy for treating CP in children.Methods:The following electronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…It follows the meridian theory and works on the organs, energy channels in muscle groups and points on the body using the same principles as acupuncture, except hands and fingers are used instead of needles [ 73 ]. It is combined with anatomical and pathological diagnosis in order to achieve dredging meridian, removes pathogenic factors and has a curative effect of a harmonic balance of Yin-Yang [ 74 ]. Tuina can act on the subcutaneous muscular layer; enhance local blood circulation, lymph circulation, tissue metabolism of the skin, can regulate physiological and pathological states, unblock meridians, and harmonize Qi (total life energy).…”
Section: Discussionmentioning
confidence: 99%
“…It follows the meridian theory and works on the organs, energy channels in muscle groups and points on the body using the same principles as acupuncture, except hands and fingers are used instead of needles [ 73 ]. It is combined with anatomical and pathological diagnosis in order to achieve dredging meridian, removes pathogenic factors and has a curative effect of a harmonic balance of Yin-Yang [ 74 ]. Tuina can act on the subcutaneous muscular layer; enhance local blood circulation, lymph circulation, tissue metabolism of the skin, can regulate physiological and pathological states, unblock meridians, and harmonize Qi (total life energy).…”
Section: Discussionmentioning
confidence: 99%
“…Tuina manipulations have been performed along specific channels Evidence-Based Complementary and Alternative Medicine (meridians) and on confirmed acupuncture points on the body surface of patients for the purpose of alleviating symptoms of diseases [23]. Some clinical trials have reported that Tuina is beneficial for motor function improvement, intellectual development, and improvement of self-care abilities and the daily life of children with CP [10,24,25]. Moreover, animal experiments have shown that Tuina improved the motor balance and cognitive functions of HIE rats, the underlying mechanism of which was associated with the regulation of inflammation and genome-wide DNA hydroxymethylation levels [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…As a physical therapy derived from traditional Chinese medicine (TCM), Tuina has shown multiple effects on a diverse set of diseases, including CP-although the effects of Tuina in CP remain controversial. Previous studies have indicated that Tuina may be used to improve the cognitive and motor functions and self-care abilities of children with CP [10][11][12][13]. Nevertheless, the precise mechanism of Tuina to treat CP is still unclear, which limits its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In the article, “Tuina for children with cerebral palsy: A protocol for a systematic review”, [ 1 ] which appeared in Volume 97, Issue 4 of Medicine , Dr. Taipin Guo's name appeared incorrectly as Tainpin Guo.…”
mentioning
confidence: 99%